ICT in schools of the Frances Baard district in Northern Cape - Thekisho, Paulinah Mamotolo (My University, 2015)
The post apartheid government of South Africa adopted bold policies aimed at investing in the use of computers in South African schools. The decision to invest in computers in schools was driven by a global agenda aimed to fast track development in Africa with the aim to empower a future citizenry to participate in a competitive global economy. Investing in computers is compounded by apartheid legacy issues, caused by close to five decades of segregationist policies responsible for huge inequalities. This study investigated the factors that played a role in promoting the use of computers in schools. The purpose of this exploratory study was to identify factors that promote or inhibit the use of computers in schools in Frances Baard District of the Northern Cape secondary schools. The findings are that lack of access, lack of training, lack of technical support is some of the factors that impede the use of computers in schools.
Keywords: Educational technology ;Computer-assisted instruction -- South Africa -- Northern Cape.